The role of digital B2B platforms with industry 4.0 technological ecosystems(integration of cloud computing, artificial intelligence and internet of things) as a growth lever - Ololade A. Shonubi (Sustainable Futures)
This study investigates how digital business-to-business (B2B) platforms transform manufacturing industries through Industry 4.0 ecosystems and emerging digital technologies such as AI, Cloud Computing, and IoT. Employing methodological triangulation, the research provides comprehensive insights into platform-enabled digital transformation pathways through systematic literature review, case study analysis, and secondary data examination.The research applies the Technology-Organisation-Environment (TOE) framework to develop the Growth Lever Framework for Digital B2B Platforms, using Alibaba.com as a comprehensive case study. By analysing digital transformation mechanisms, the study reveals critical insights into the orchestration of global digital platforms as technological ecosystems.Key findings highlight the complex dynamics of digital platform evolution; Technological integration success is contingent upon platform governance structures, with users prioritising efficient supplier communication and comparison systems. Resource optimisation emerges as a critical mechanism, enabling manufacturers to strategically allocate digital transformation investments while maintaining operational capabilities. Significant regional variations emerge between emerging markets (Pakistan, Brazil, India) and developed markets (UK, Canada), revealing the profound impact of regulatory environments on platform success.The Growth Lever Framework and Digital Platform Ecosystem Technological Readiness Model (DPETRM) created within this study contribute theoretical perspectives by conceptualising how B2B platforms drive manufacturing transformation. By examining the interplay of technological capabilities, organisational structures, and environmental factors, the research offers strategic guidance for stakeholders navigating increasingly complex and emerging digital technological ecosystems.